2015
DOI: 10.1007/s11740-015-0602-2
|View full text |Cite
|
Sign up to set email alerts
|

Criticality analysis of spare parts management: a multi-criteria classification regarding a cross-plant central warehouse strategy

Abstract: Today an efficient warehouse and inventory management of spare parts for production machinery is essential for service organizations. Optimal strategies in procurement, stocking and supply play an important role for serviceability in spare parts management. In this context, individual item criticality should be considered, which describes how crucial a spare part is. This paper presents a three-dimensional classification approach for spare parts regarding a cross-plant central warehouse strategy of a service n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
0
27
0
3
Order By: Relevance
“…It is noteworthy to emphasise that in the aviation industry, both 'operational criticality' and 'technical characteristics' are suggested to be the most important criteria due to the stringent regulation imposed to ensure passenger safety (Vieira and Loures, 2016), while 'supply characteristics' is considered to be less important and moderated by the collaborative strategies among the aviation partners, which lead to an incresed certainty in the supply continuity (Kilpi et al, 2009). The developed AHP model enabled a practical and relevant multi-criteria classification of aircraft spare part thanks to its ability to i) aggregate both qualitative and quantitative criteria (Stoll et al, 2015), ii) structure and cluster all factors in hierarchical manner (Saaty, 2008;Saaty, 1990), iii) enable different weight in each criterion to be considered, iv) provide a transparent (Molenaers et al, 2012) and user friendly decisionmaking framework (Roda et al, 2014) and v) integrate the decision diagram logic to solve the specific aircraft spare part essentiality classification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy to emphasise that in the aviation industry, both 'operational criticality' and 'technical characteristics' are suggested to be the most important criteria due to the stringent regulation imposed to ensure passenger safety (Vieira and Loures, 2016), while 'supply characteristics' is considered to be less important and moderated by the collaborative strategies among the aviation partners, which lead to an incresed certainty in the supply continuity (Kilpi et al, 2009). The developed AHP model enabled a practical and relevant multi-criteria classification of aircraft spare part thanks to its ability to i) aggregate both qualitative and quantitative criteria (Stoll et al, 2015), ii) structure and cluster all factors in hierarchical manner (Saaty, 2008;Saaty, 1990), iii) enable different weight in each criterion to be considered, iv) provide a transparent (Molenaers et al, 2012) and user friendly decisionmaking framework (Roda et al, 2014) and v) integrate the decision diagram logic to solve the specific aircraft spare part essentiality classification.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the primary advantages of the AHP method are the transparency and the user friendliness (Molenaers et al, 2012). A study by Stoll et al, (2015) also assigns a spare part classification to inventory management. The paper presents a three-dimensional spare-part classification using a decision tree and AHP.…”
Section: Difficult Practical Applicabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of inventory centralization dates back to the 1960s (Das and Tyagi, 1997).The main body of research within inventory management of spare parts agree that centralization is the best way to achieve cost savings (Tiacci and Saetta, 2010;Karsten et al, 2012;Braglia and Frosolini, 2013;Cohen et al, 2009;Stoll et al, 2015;Karsten and Basten, 2014). Inventory centralization is in this paper defined as the physical consolidation of local warehouses, procurement and distribution functions to a few (single) main warehouses.…”
Section: Introductionmentioning
confidence: 99%